Congenital ichthyoses: European guidelines of care, part two. (1st March 2019) - Mazereeuw‐Hautier, J.; Hernández‐Martín, A.; O'Toole, E.A.; Bygum, A.; Amaro, C.; Aldwin, M.; Audouze, A.; Bodemer, C.; Bourrat, E.; Diociaiuti, A.; Dolenc‐Voljč, M.; Dreyfus, I.; et al.
Summary: Ichthyosis is the term used to describe continual and widespread scaling of the skin. There are several genetic types which are present from birth and persist life‐long – the "congenital ichthyoses". There is no agreed treatment ‐ different doctors use different approaches, so this group of experts from all over Europe worked together to develop guidelines. They reviewed the medical literature and met to discuss the evidence and to make recommendations. A separate paper (Part 1) covered treatments for the skin condition itself. This paper, Part 2, provides guidelines for managing complications of the congenital ichthyoses. Itch, pain and infections are common, particularly fungal infection, and cancers sometimes occur. Tight skin often prevents eyelids from shutting properly so the eye surface must be protected with lubricant; eyelid massage may help and retinoid medicine may soften tight skin but can dry the eyes further. Surgical options include injecting filler or grafting extra skin to the eyelid: if the patient's own ichthyotic skin is used the problem eventually recurs and mucous membrane from inside the mouth is a promising alternative. Hearing is commonly affected: blockage of ears by a build‐up of skin may be prevented by regular oil drops but syringing or suction may be necessary. In children, growth may be affected and vitamin D supplements are usually recommended. There are special considerations for newborn babies and those with complex ichthyotic disorders such as Netherton Syndrome, epidermolytic ichthyosis and Ichthyosis Prematurity Syndrome. These treatment guidelines should help to improve outcomes and quality of life for patients with congenital ichthyoses.